2013
DOI: 10.1021/jf304833d
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Imaging for Structural Analysis of Frankfurter Sausages Subjected to Salt Reduction and Salt Substitution

Abstract: In this study, the effects of NaCl, KCl, and MgSO4 in various concentrations on structural and sensory properties of frankfurter sausages were investigated. FTIR was used to analyze the overall homogeneousness of the sausages by simultaneously following the distribution of main sausage ingredients, i.e., proteins, fats, and starch. A more homogeneous distribution of the main ingredients was observed with higher concentration of added salts, while it was most pronounced for the MgSO4 recipe. Furthermore, FTIR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Multiplicative scatter correction (MSC), and later extended MSC (EMSC), was developed in the 80s for applications in near‐infrared (NIR) spectroscopy in food science, and today, EMSC is one of the major frameworks for model‐based pre‐processing in vibrational spectroscopy. In the last years, EMSC has particularly attracted attention within IR spectroscopy for selective correction of features like sample thickness and temperature, water vapour, carbon dioxide and salt concentration . An EMSC‐based algorithm for estimating and correcting the contribution of Mie scattering effects in Fourier‐transform (FT) IR microspectroscopy of cells has also recently gained attention …”
Section: Introductionmentioning
confidence: 99%
“…Multiplicative scatter correction (MSC), and later extended MSC (EMSC), was developed in the 80s for applications in near‐infrared (NIR) spectroscopy in food science, and today, EMSC is one of the major frameworks for model‐based pre‐processing in vibrational spectroscopy. In the last years, EMSC has particularly attracted attention within IR spectroscopy for selective correction of features like sample thickness and temperature, water vapour, carbon dioxide and salt concentration . An EMSC‐based algorithm for estimating and correcting the contribution of Mie scattering effects in Fourier‐transform (FT) IR microspectroscopy of cells has also recently gained attention …”
Section: Introductionmentioning
confidence: 99%
“…The comprehensive disruption of muscle structure by ISP may also be important in aligning proteins for gel formation during heating, thus reducing NaCl demand to induce the same effect (Chang, Feng, & Hultin, 2001;Wright & Lanier, 2005). Additionally, the increase of potassium content in the ISPCgels (Figure 1) might result in more β-sheets that was conducive to obtain the good texture at 1% NaCl (Choi & Ma, 2007;Perisic, Afseth, Ofstad, Scheel, & Kohler, 2013). Our results did demonstrate that the gel-type meat products created by the ISP process with low sodium content had good textural properties that were equal to those produced by the conventional process with high sodium content.…”
Section: Textural Propertiesmentioning
confidence: 55%
“…However, another work concluded that the addition of NaCl to myosin from catfish treated by the ISP process reduced the content of α-helix to 15% and this occurrence corresponded to an increase in β-sheet content (Raghavan & Kristinsson, 2008). In addition, the increase of potassium content in the ISP-recovered proteins also enhanced the signal intensity of the β-sheets (Perisic et al, 2013). The reduced α-helix and increased β-sheet levels prior to heating is conducive to the formation of a three-dimensional gel network and increase hardness, but decreases the binding strength of water to protein molecules and the capacity of the gels to trap water in the matrix (Choi & Ma, 2007;Liu et al, 2008).…”
Section: Whcmentioning
confidence: 99%
See 2 more Smart Citations